2018
DOI: 10.1111/wej.12387
|View full text |Cite
|
Sign up to set email alerts
|

One‐step synthesis of NiO nano‐photocatalyst by wire explosion process and its application in photocatalytic degradation of Methyl tert‐butyl ether

Abstract: The use of the gasoline additive methyltert‐butyl ether (MTBE) has caused serious concern about groundwater and surface water contamination. In this study, UV light/ NiO nano‐photocatalyst (NiONP) system was firstly used to degradation of MTBE in contaminated water. A low‐cost and environmentally clean exploded‐wire plasma technique based on cheap solid nickel source is developed for preparation of NiONP. Optical, magnetic and physicochemical properties were successfully characterized using DRS, VSM, XRD, SEM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The possible mechanism of Pt/Au NPs@Co 3 O 4 to the selective catalysis of MSBE was speculated by comparing the structures of MTBE and MSBE. The CTL test (Figure 5) showed that MSBE presented a strong CTL response, while MTBE showed no signal, therefore the functional groups involved in the CTL signaling response will not be methoxyl groups, which are present in both MTBE and MSBE [34,35]. The possible CTL reaction process of MSBE is shown as a response equation in Figure 6.…”
Section: The Catalytic Performance Of the Cataluminescence Sensormentioning
confidence: 99%
“…The possible mechanism of Pt/Au NPs@Co 3 O 4 to the selective catalysis of MSBE was speculated by comparing the structures of MTBE and MSBE. The CTL test (Figure 5) showed that MSBE presented a strong CTL response, while MTBE showed no signal, therefore the functional groups involved in the CTL signaling response will not be methoxyl groups, which are present in both MTBE and MSBE [34,35]. The possible CTL reaction process of MSBE is shown as a response equation in Figure 6.…”
Section: The Catalytic Performance Of the Cataluminescence Sensormentioning
confidence: 99%